Fysioterapeuttiopiskelijoiden moniammatilliseen osaamiseen yhteydessä olevat tekijät - Tervonen, Kirsi (2024)
The use of interdisciplinary skills in the rehabilitation process aims to improve the appropriate use of health professionals' skills for the benefit of the rehabilitated person and to reduce the burden on the health system. Interdisciplinary training has helped to avoid duplication of work, promote better patient encounter, and achieve better rehabilitation outcomes. Only half of Finnish health care degree programs provide interdisciplinary training. The aim of this thesis was to investigate Finnish physiotherapy student's perceptions of their interdisciplinary competence and related background factors. In addition, it was investigated whether ethical competence, knowledge of roles and responsibilities and network competence explain physiotherapy student's interdisciplinary competence. The study was part of the Core Competencies of Physiotherapy Students -study and its results will be used as part of the validation of the student survey.